(untitled) (Bangladesh Journal of Botany, 2022)
In the environment, Bisphenol A (BPA) is an emerging universal pollutant and it disrupts endocrine system and is substantially toxic for living beings and significantly harmful to the plants as well. Toxicologic effects of BPA on plants is not fairly documented. In the present study, effects of BPA on growth and chlorophyll content were studied in Pisum sativum L. (pea) seedlings. After treatment of pea seeds with varying concentrations of BPA (2, 5, 10, 15, 20, and 25 mg/l) for 3 hrs at room temperature (21°C), they were sown in pots and growth viz., height of plants, fresh and dry weights of stems and leaves and chlorophyll content were recorded after 15 and 30 days from sowing. The current study confirmed that BPA can affect the growth and chlorophyll content in a dose related manner. BPA at lower concentration (2 mg/l) increased the growth in pea seedlings whereas BPA at higher concentration exhibited a significant inhibitory effect on the growth of pea seedlings. Consequently, the results of this study may be applied in future researches of environmental hazards linked to soil due to BPA as well as managing of BPA in relation to soil. Bangladesh J. Bot. 51(2): 237-245, 2022 (June)